Maskils and Musicals: Biblical Narrative and Attic Theatre, Part II - Haasbroek, Lisa Marie (Scandinavian journal of the Old Testament, 2022)
In support of scholarship which proposes a Hellenistic date for biblical literature, this study proposes that portions of the Bible are written in the style of Attic theatre plays. Part II demonstrates the ways in which biblical literature meets all criteria for Attic tragedies in Aristotle’s Poetics, using the Book of Samuel as an example. This approach offers new ways to interpret biblical literature.